Prácticas letradas académicas más allá del déficit: una revisión crítica de literatura. - Sito, Luanda; Moreno, Emilce (Enunciación)
What relationships can we derive by bringing academic literacy discussions closer to teacher education? This literature review analyzes the contributions made possible by the academic literacy perspective for language teaching in vocational training, especially for teacher and literacy pedagogy. From the New Literacy Studies (NLS), reading and writing in relation to epistemology and the construction of knowledge are explored; at the same time, the institutional relations of power and authority are taken into account, and their implications in the learning processes. Starting from this field of studies, 50 references are analyzed, either empirical research published in indexed journals published in the last ten years, or classic works in the field of literacy. The following trends are identified: 1) Academic literacy across disciplines, 2) Pedagogy of writing and reading, 3) Student university trajectories, 4) Academic literacy practices: tensions in appropriation processes, 5) Digital literacy. Taking the findings as a framework, the contributions of this critical perspective of written culture to language teaching are presented and some discussions are outlined for the future of critical praxis in teacher training.